Pengaruh Pemahaman Tentang Sistem Bunga dan Bagi Hasil terhadap Minat Menabung pada Bank Syariah - Dewi Maharani; Firdha Mulia (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2023)
This research is to assess the extent to which students' understanding is related to bank interest and the profit sharing system at conventional and Islamic banks and financial institutions, so that they can measure students' interest in saving at sharia bank. The research was conducted with a sample of students at the Muhammadiyah University of Banjarmasin. The research was conducted quantitatively with primary data. Data processing was carried out using multiple linear regression using SPSS, by testing classical assumptions and testing hypotheses. From the results of the statistical tests carried out, it was obtained that the results of the hypothesis test with the t test on variable X1 had a t count of 2.904 greater than t table, namely (2.904 > 1.68488) with a significant value of 0.006 <0.05 which indicates that the variable understanding of bank interest is partially has a positive influence on the intention to save at conventional banks. Meanwhile, X2 has a t count of 1.924 which is greater than the t table (1.924 > 1.68488) with a significant value of 0.062 > 0.05) indicating that the variable understanding of profit sharing partially has no positive effect on students' interest in saving at Islamic banks. This means that students do not understand the profit sharing system at Islamic banks, so students are less interested in using Islamic banking services.